Empowering Rural Bank in the Era of Globalisation : Legal Reforms and Pancasila Values - Monica Puspa Dewi Suganda Putri (International Journal of Law, Crime and Justice, 2025)
The inability of rural banks to adapt to the changing global landscape, particularly owing to globalisation, could also have adverse effects on economically disadvantaged populations. This research aims to examine the dynamics of regulating rural banks in Indonesia, the pressing need for legal reforms in rural banks to address the problems posed by globalisation, and the legal reforms for rural banks that are based on the Values of Pancasila. The study methodology employed is the Normative Juridical approach. The research findings suggest that initially, the licencing and activities of the rural bank required permission from the Minister of Finance. However, after the amendment of Law Number 7 of 1992 concerning Banking with Law Number 10 of 1998, the licence for rural banks is now granted by the leadership of Bank Indonesia, as stated in Article 16 paragraph. Globalisation has a significant impact on community life, leading to the emergence of new requirements. One of these requirements is the need for easier transactions, which can be achieved through the digitalisation of banking or the provision of electronic banking facilities. Consequently, legal reforms for banking institutions need to be implemented, taking into account the noble values of the nation as reflected in the moral principles of Pancasila. These values include morality, respect, protection of human rights without discrimination, unity, social justice in the economic and community sectors, and the realisation of people’s sovereignty and adherence to the law.